Heyde’s syndrome: a systematic review of case reports - Bibek Saha; Eric Wien; Nicholas Fancher; Melissa Kahili-Heede; Nathaniel Enriquez; Alena Velasco-Hughes (BMJ Open Gastroenterology)
Objective Heyde’s syndrome (HS), a rare condition characterised by a unique relationship between severe aortic stenosis and angiodysplasia, is often diagnosed late increasing the risk for a prolonged hospital course and mortality in the elderly. The leading hypothesis explaining the aetiology of HS is acquired von Willebrand syndrome (AVWS) but not all studies support this claim. While individual cases of HS have been reported, here we present the first systematic review of case reports and focus on the prevalence of AVWS.Design A systematic search was conducted through PubMed/MEDLINE, CINAHL-EBSCO, Web of Science and Google Scholar since inception. The resulting articles were screened by two independent reviewers based on inclusion criteria that the article must be a case report/series or a letter to the editor in English describing HS in an adult patient.Results Seventy-four articles encompassing 77 cases met the inclusion criteria. The average age was 74.3±9.3 years old with a slight female predominance. The small intestine, especially the jejunum, was the most common location for bleeding origin. Capsule endoscopy and double balloon enteroscopy were superior at identifying bleeding sources than colonoscopy (p=0.0027 and p=0.0095, respectively) and oesophagogastroduodenoscopy (p=0.0006 and p=0.0036, respectively). The mean duration from symptom onset to diagnosis/treatment of HS was 23.8±39 months. Only 27/77 cases provided evidence for AVWS. Surgical and transcutaneous aortic valve replacement (AVR) were superior at preventing rebleeding than non-AVR modalities (p<0.0001).Conclusion Further research is warranted for a stronger understanding and increased awareness of HS, which may hasten diagnosis and optimal management.